Pilot Study of Intra-Aortic Balloon Occlusion to Limit Morbidity in Patients with Adherent Placentation Undergoing Cesarean Hysterectomy - Elizabeth Blumenthal; Rashmi Rao; Aisling Murphy; Jeffrey Gornbein; Richard Hong; John M. Moriarty; Daniel A. Kahn; Carla Janzen (Thieme Medical Publishers, Inc., 2018)
Abstract Objective We study whether using an intra-aortic balloon (IAB) during cesarean hysterectomy decreases delivery morbidity in patients with suspected morbidly adherent placentation. Study Design This is a retrospective cohort study of deliveries complicated by suspected abnormal placentation between 2009 and 2016 comparing maternal and neonatal outcomes with an IAB placed prior to cesarean hysterectomy versus no IAB. The primary outcome included quantified blood loss (QBL). Results Thirty-five cases were reviewed, 16 with IAB and 19 without IAB. No difference was seen in median QBL between the two groups (1,351 vs. 1,397 mL; p = 0.90). There were no significant differences in overall surgical complications (19% IAB, 21% no IAB; p = 0.86), bladder complications (12 vs. 21%; p = 0.66), intensive care unit admissions (12 vs. 26%; p = 0.41), surgical duration (2.9 vs. 2.8 hour; p = 0.83), or blood transfusions (median 2 vs. 2; p = 0.27) between the two groups. There was one groin hematoma at the balloon site that was managed conservatively. There were no complications involving thrombosis or limb ischemia in the IAB group. Conclusion While we did not detect statistically significant differences, larger studies may be warranted given the potential for extreme morbidity in these cases. This study highlights the potential use of an IAB in the management of these cases.